Family Medicine : Principles and Practice - Paulman, Paul M.; Taylor, Robert B.; Paulman, Audrey A.; Nasir, Laeth S. (Springer International Publishing : Imprint: Springer, 2017)
The seventh edition of this classic reference book has been vastly updated from its previous edition to reflect the many changes in clinical medicine since 2003. Family Medicine: Principles and Practice, 7th Edition, is a must-have reference for medical students, residents and practicing physicians, nurse practitioners and physician assistants actively involved in patient care. New topics included in this edition include: recent changes in screening requirements and immunization schedules; new antibiotics used in primary care; inflammatory biomarkers in diagnosis and management of common diseases; personality disorders; the patient-centered medical home; electronic health records in office practice; chronic pain management; pediatric and adolescent obesity; pelvic pain syndromes; concussion in sports and other trauma; health literacy; venous thromboembolic disease; management of opiate dependence; vaginal birth after cesarean section; autism spectrum disorders and Asperger syndrome; older drivers, dementia and safety; infections with public health significance; and managing mentally ill patients in primary care. This book is organized into short, focused chapters almost exclusively dedicated to topics relevant to daily practice. All lead authors are themselves accomplished family physicians who can specifically address the needs, concerns, and interests of this crucial profession.- Resumé vydavatel
Keywords: praktičtí lékaři; geriatrie; pediatrie; vnitřní lékařství; general practitioners; geriatrics; pediatrics; internal medicine; elektronické knihy; sborníky; electronic books; papers of several authors